2013
DOI: 10.1111/aas.12108
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of changes in cardiac index and fluid responsiveness: a comparison of Nexfin and transpulmonary thermodilution

Abstract: The Nexfin cannot be used to measure rapid changes in cardiac index following fluid challenge and to predict fluid responsiveness after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 32 publications
1
23
4
Order By: Relevance
“…Other studies have also reported favourably on the Nexfin's ability to measure cardiac output accurately, e.g., compared with rebreathing methods, 111 or with transthoracic Doppler. 112 These results contrast with other studies that reported far inferior performance of the Nexfin device when comparing the noninvasively derived cardiac output measurements with thermodilution in critically ill patients 113,114 and cardiac ultrasound. 115 It is important to point out that, relative to other noninvasive cardiac output devices (e.g., over 3,000 patients in 16 studies comparing the FloTrac [uncalibrated] with thermodilution, over 1,400 patients in nine studies comparing the PiCCO [calibrated] with thermodilution, and almost 400 patients in three studies comparing the LiDCO [calibrated] with thermodilution), 107 there are very few data comparing volume-clamp-based estimates of SV or cardiac output with gold standards.…”
Section: Technologic Principlescontrasting
confidence: 58%
“…Other studies have also reported favourably on the Nexfin's ability to measure cardiac output accurately, e.g., compared with rebreathing methods, 111 or with transthoracic Doppler. 112 These results contrast with other studies that reported far inferior performance of the Nexfin device when comparing the noninvasively derived cardiac output measurements with thermodilution in critically ill patients 113,114 and cardiac ultrasound. 115 It is important to point out that, relative to other noninvasive cardiac output devices (e.g., over 3,000 patients in 16 studies comparing the FloTrac [uncalibrated] with thermodilution, over 1,400 patients in nine studies comparing the PiCCO [calibrated] with thermodilution, and almost 400 patients in three studies comparing the LiDCO [calibrated] with thermodilution), 107 there are very few data comparing volume-clamp-based estimates of SV or cardiac output with gold standards.…”
Section: Technologic Principlescontrasting
confidence: 58%
“…While the present study is the first validation study for CNCO, another technology for the noninvasive assessment of CO based on the volume clamp method [i.e., ClearSight system (Edwards Lifesciences, Irvine, CA, USA); formerly known as Nexfin system (BMEye, Amsterdam, The Netherlands)] has been evaluated in clinical studies before-with inconsistent results. While Broch et al [22] demonstrated that the Nexfin system allows CO estimation in cardiac surgery patients with a percentage error of \30 % when compared with transpulmonary thermodilution, higher percentage errors between 38 % and 58 % were reported in other clinical studies evaluating the system in cardiac surgery patients in comparison with pulmonary artery or transpulmonary thermodilution [23][24][25][26]. In 45 mixed ICU patients, Ameloot and colleagues [27] revealed a percentage error of 36 % between Nexfin-CO and CO determined by transpulmonary thermodilution.…”
Section: Discussionmentioning
confidence: 99%
“…The technique is not applicable in low flow in the finger arteries, hypothermia, or peripheral oedema. ClearSight CO has been studied in cardiac surgical patients against PAC and PiCCO and has demonstrated a limited accuracy and precision and a high percentage error (weighted average of 41%) [83][84][85][86][87][88][89][90][91], but reliably track preload-induced changes in CO [92][93][94]. ClearSight was less accurate in patients with low CO, hypothermia and high SVR but performed better in patients with high CO [95].…”
Section: Clearsight System (Edwards Lifesciences® -Usa)mentioning
confidence: 99%